Living in endemic area for infectious diseases is associated to differences in immunosenescence and inflammatory signatures - Coelho, Monique Macedo; Moreira, Felipe Caixeta; Zuccherato, Luciana Werneck; Ventura, Lucas Haniel de Araújo; Camatta, Giovanna Caliman; Starling-Soares, Bernardo; Torres, Lícia; Durso, Danielle Fernandes; Sato, Hugo Itaru; da Costa, Murilo Soares; Guimarães, Henrique Cerqueira; Barbuto, Rafael Calvão; et al. (Frontiers in Immunology, 2025)
Research on aged individuals from developed countries show that lifestyle factors such as diet, physical activity, stress, smoking, and sleep quality impact aging. However, other relevant factors may influence aging in less-studied populations, such as Brazilian cohorts. This study aimed to analyze immunosenescence profile of individuals living in an endemic area for several infectious diseases in Brazil. We showed that these individuals exhibited accelerated epigenetic aging and increased production of IL-12p70, IL-17A, and IL-9. Production of inflammatory mediators IL-12p70, IL-6, IL-1β, IL-2, and IL-1ra in individuals with flu-like symptoms and those with COVID-19 was higher among residents in endemic areas than in residents from a control non-endemic area. Furthermore, residents of the endemic area had a more prominent inflammatory profile during viral infection and a different pattern of plasma mediators when compared to residents of a non-endemic area. Our data suggests that these two cohorts had specific immune signatures regardless of the presence or the type of infection at study. Therefore, we demonstrated that there were distinct patterns of immune responses and epigenetic aging depending on the environment the individuals live in. These observations add a layer of diversity to the studies of human aging by including individuals from less represented regions.